Sarcopenia and Osteoporosis: Two Sides of the Same Coin - Abhijith Anil; Sandesh Agrawal; Mikeson Panthackel; Bharat Dave (Indian Spine Journal)
Osteosarcopenia is a condition characterized by the coexistence of both osteoporosis and sarcopenia. It is more prevalent in aging populations. Due to the heightened risk of falls, fragility fractures, and associated morbidity and mortality, osteosarcopenia results in a significant healthcare burden. The pathogenesis of osteosarcopenia is multifactorial, involving mechanical, biochemical, genetic, and lifestyle-related factors. The role of cross-talk between muscle and bone, mediated by various myokines, osteokines, and signaling pathways, has been extensively studied. Epidemiological studies reveal a global prevalence of osteosarcopenia to be 18.5%, with a higher incidence in older adults, particularly women. Diagnosis relies on assessing both bone mineral density and muscle mass. Tools like dual-energy X-ray absorptiometry (DXA), along with functional tests for muscle strength and physical performance, are useful in the diagnosis of osteosarcopenia. Management strategies include physical activity, nutritional supplementation, and pharmacological interventions. Resistance training combined with protein supplementation has shown promise in improving muscle strength and function, though evidence specific to osteosarcopenia is sparse. Emerging therapies, including anabolic agents and potential gene therapy, offer hope for more targeted treatment approaches in the future. Recognizing osteosarcopenia as a distinct clinical entity helps in developing management strategies. Further research is needed to refine diagnostic criteria, explore novel therapeutic interventions, and improve patient outcomes.